Ultrasound guided quadratus lumborum block for analgesia after cesarean delivery: case series - Sebbag,Ilana (2017)
Abstract Introduction: The majority of women having planned cesarean section receive spinal anesthesia for the procedure. Typically, spinal opioids are administered during the same time as a component of multimodal analgesia to provide pain relief in the 16-24 h period postoperatively. The quadratus lumborum block is a regional analgesic technique that blocks T5-L1 nerve branches and has an evolving role in postoperative analgesia for lower abdominal surgeries and may be a potential alternative to spinal opioids. If found effective, it will have the advantage of a reduction in opioid associated adverse effects while providing similar quality of analgesia. Methods: We performed bilateral quadratus lumborum block in 3 women who received a spinal anesthetic for a cesarean delivery and evaluated their post-operative opioid consumption and patient satisfaction. Results: In all 3 patients, there was no additional opioid consumption during the first 24 h after the block. Numeric Rating Scale (NRS) for pain was less than 6 for the first 24 h. Women were all very satisfied with the quality of pain relief. Discussion: Quadratus lumborum block may be a promising anesthetic adjuvant for post-cesarean analgesia. Further randomized controlled trials are needed to compare the efficacy of the quadratus lumborum block with intrathecal opioids.